Incremental Feature Learning for Cybersecurity under Evolving Feature Spaces - Lemos, Rafael S.; Ribeiro, Davyson S.; Ponte, Francisco R. P. da; Mattos, César Lincoln C.; Rodrigues, Emanuel B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Cybersecurity systems continuously evolve by incorporating new data attributes, requiring machine learning models to adapt without costly retraining. This work proposes two Incremental Feature Learning (IFL) approaches for intrusion detection and vulnerability risk classification: a hybrid Naive Bayes model and a Multilayer Perceptron with partial weight freezing. Experimental results show that both approaches effectively adapt to progressively expanding feature spaces while maintaining competitive computational efficiency. The proposed MLP achieved over 93% accuracy for intrusion detection, whereas the incremental strategies reduced learning cost and memory consumption without full model retraining.